Bonjour j'ai besoin d'aide pour un devoir de maths :


Factorisez les expressions suivantes : D = (6x – 2) (x + 7) + (3x + 1)(x + 7) ; E =(3x – 1)² – (3x–1) (4x + 5) ; F= 9x² + 24x + 16 G = 16 – (2x – 3)².


Répondre :

bonjour

D = (6x – 2) (x + 7) + (3x + 1)(x + 7)

    =  ( x + 7 ) ( 6 x - 2 + 3 x + 1 )

    = ( x + 7 ) ( 9 x - 1 )

E =(3x – 1)² – (3x–1) (4x + 5)

   = ( 3 x - 1 ) ( 3 x - 1 - 4 x - 5 )

   = ( 3 x - 1 ) ( - x - 6 )

F= 9x² + 24x + 16

   = ( 3 x + 4 )²

G = 16 – (2x – 3)².

   = ( 4 + 2 x - 3 ) ( 4 - 2 x + 3)

   = ( 2 x + 1 ) ( - 2 x + 7 )

Bonjour,

Factoriser:

D = (6x – 2) (x + 7) + (3x + 1)(x + 7)

   = (x+7)(6x-2+3x+1)

   = (x+7)(9x-1)

E =(3x – 1)² – (3x–1) (4x + 5)

  = (3x-1)(3x-1-(4x+5))

  = (3x-1)(3x-1-4x-5)

  = (3x-1)(-x-6)

  = - (3x-1)(x+6)

F= 9x² + 24x + 16

  = 9x²+2*4*3x+4²

  = (3x+4)²

G = 16 – (2x – 3)²

   =  4²- (2x – 3)²

   = (4-(2x-3)(4+2x-3)

   = (4-2x+3)(2x+1)

   = (-2x+7)(2x+1)

   = - (2x-7)(2x+1)